Instructional Modifications in Inclusive Early Childhood Education: A Case Study of Teaching Strategies for Children with Autism in Yogyakarta - Maulidah, Winda Syafaatin; Mufalakhah, Kurnia (Global Educational Research Review, 2024)
Purpose – This study investigates the application and effectiveness of instructional modifications in an inclusive classroom, specifically focusing on a child with autism, at TK ABA Karanganyar, Yogyakarta. The research addresses the knowledge gap in inclusive education by exploring how teaching strategies can be adapted to meet the diverse needs of students, particularly children with special needs (CSN), and foster their academic and social development.. Design/Methods/Approach – A qualitative case study method was employed, utilizing semi-structured interviews, direct classroom observations, and document analysis. Data were collected from the classroom teacher, principal, and students, including one child with autism, over multiple observation sessions. Analysis was conducted using Miles and Huberman's interactive model, ensuring data triangulation through cross-referencing interviews, observations, and school documents. Findings – The study found that flexible and individualized instructional modifications—such as adapting learning activities and providing intensive assistance—promote engagement and development in children with special needs. These modifications not only support the child with autism but also enhance peer interactions, fostering a more inclusive classroom environment. However, resource constraints, including the lack of specialized aides and visual tools, were identified as challenges in fully implementing inclusive strategies. Originality/Value – This research contributes to the literature by demonstrating that effective inclusive education can be achieved through teacher-initiated instructional modifications, even in the absence of formal inclusion programs. The findings provide valuable insights into creating inclusive environments in resource-limited settings, emphasizing teacher flexibility and creativity. Practical Implications – The results offer practical recommendations for educators on implementing flexible, needs-based strategies in inclusive classrooms. Policymakers are encouraged to support inclusive education through targeted teacher training and resource allocation. Keywords Inclusive education, instructional modification, early childhood, autism. Paper type Research paper